Performance Analysis of Nanowire ISFET Biosensor Towards Bovine Serum Albumin and Liposome (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Proteins are necessary to all living organisms for both structural and functional reasons. However, due to their breakdown, some proteins, including Bovine Serum Albumin (BSA) and Liposome, could cause detrimental effects on cells and tissues. Due to its high detection sensitivity, the potential for mass production, and affordable manufacture, the ion-sensitive field-effect transistor (ISFET) biosensor has become increasingly prominent in clinical research for the detection of biomolecules. BSA and Liposome are the target proteins, while collagen is the bioreceptor. ISFET biosensor with a structure of cylindrical nanowire was simulated and examined. The settling time and sensitivity of the biosensor were modeled using Nanohub BioSensorLab software. The cylindrical nanowire ISFET biosensor can be enhanced by reducing the buffer ion concentration, increasing the radius, and increasing the oxide thickness. Compared to liposomes, BSA provides a lower settling time. This is because the diffusion coefficient of liposomes is 3.6 times lower than BSA. Furthermore, settling time is reduced when the analyte concentration is increased. The results are compared with planar ISFET, considered one-dimensional (1D) architecture. The planar ISFET exhibited a quicker settling time than the cylindrical nanowire biosensor. Furthermore, as the amounts of protein and analyte increased, the settling time reduced. The cylindrical nanowire biosensor needs to be in radius of 100nm and 10nm of oxide thickness with 0.1M buffer concentration for it to achieved the highest sensitivity. These results could facilitate researchers to produce the desirable ISFET sensor for different types of proteins.